Effect of Sb addition on SbxSn1‐xS thin films: The structural, morphological, and linear/nonlinear optical changes for optoelectronic applications. Issue 10 (1st June 2022) - Parida, A.; Alagarasan, D.; Ganesan, R.; Vardhrajaperumal, S.; Naik, R.
Abstract: The current paper reports the changes in the structural and optical properties of antimony‐doped tin sulfide ternary (Sb x Sn1‐ x S) ( x  = 0, 0.05, 0.1, 0.15, 0.2) thin films synthesized by the thermal evaporation technique on a glass substrate. Structural characterization techniques such as X‐ray diffraction and Raman spectroscopy of the prepared sample revealed that the thin films are crystalline in nature. The nanoflake‐like structure was found from the surface morphological analysis performed by field emission scanning electron microscopy. The concentration of the compositional elements was confirmed from the energy dispersive X‐ray analysis. The linear and nonlinear optical parameters were calculated by using the transmission data obtained from UV–vis spectroscopy in the range of 800–1100 nm. The optical measurements showed an increase in transmittance and shifting of the absorption edge. The optical bandgap increased (1.239–1.378 eV) and the refractive index decreased with the increase of Sb concentration, satisfying the Moss rule. The nonlinear susceptibility and the nonlinear refractive index ( n 2 ) decreased with Sb content. The changes in both linear and nonlinear parameters by varying the antimony doping concentration could be helpful for controlling the optical properties of Sb x Sn1‐ x S thin films and could be a suitable candidate for many photonics and optoelectronic applications. Abstract : The effect of Sb doping in SnS alloys that decreases in transmission and increase in optical bandgap and simultaneous decrease in non‐linear susceptibility.